2011
DOI: 10.1007/s00405-011-1686-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of radiotherapy on laryngeal intrinsic muscles

Abstract: Ionizing radiation as a cancer therapy is associated with a variety of undesirable side effects. Consequently, radiotherapy can negatively affect neuromuscular function. Clinical observations have identified problems with swallowing and voice function. Our study aims to evaluate the impact of radiotherapy on laryngeal soft tissues using image analysis to quantify its effect on the structure of the vocalis and thyroarytenoid muscles. Case control study, retrospective analysis. We collected total laryngectomy sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
1
22
0
1
Order By: Relevance
“…Due to a better radiotolerance, the exposure dose of skeletal muscle was usually ignored compared with that of the organs at risk, such as spinal cord, lung, and small intestine, in the radiotherapy planning. Skeletal muscle injury induced by high-dose irradiation has been commonly reported, resulting in myasthenia, abnormality of the muscular tension, fatigue, pain, convulsion, and dysfunction (Bey et al, 2007;Gillette et al, 1995;Krasin et al, 2012;Tedla et al, 2012). For instance, difficulty in opening the mouth and trismus were evoked by radiation-induced injury to masticatory muscles in the patients with nasopharyngeal neoplasms and oropharyngeal neoplasms (Krasin et al, 2012;Marcus and Tishler, 2010).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Due to a better radiotolerance, the exposure dose of skeletal muscle was usually ignored compared with that of the organs at risk, such as spinal cord, lung, and small intestine, in the radiotherapy planning. Skeletal muscle injury induced by high-dose irradiation has been commonly reported, resulting in myasthenia, abnormality of the muscular tension, fatigue, pain, convulsion, and dysfunction (Bey et al, 2007;Gillette et al, 1995;Krasin et al, 2012;Tedla et al, 2012). For instance, difficulty in opening the mouth and trismus were evoked by radiation-induced injury to masticatory muscles in the patients with nasopharyngeal neoplasms and oropharyngeal neoplasms (Krasin et al, 2012;Marcus and Tishler, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…The exposure of the pharyngeal constrictor muscle to high-dose irradiation resulted in dysphagia and even longterm use of tube feeding in patients with head and neck cancer (Caudell et al, 2010;Gokhale et al, 2010). Phonatory and swallowing dysfunction was evoked by radiation-induced thyroarytenoid injury (Tedla et al, 2012). Pectoralis muscle injury and necrosis, together with skin damage, were reported in the patients with breast cancer after high-dose irradiation, resulting in intractable chronic ulcer (Rigotti et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have characterized pathological changes in laryngeal structural levels in human specimens . It is believed that radiation‐induced fibrosis is critical to late effects of radiation damage to the larynx.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms by which radiation leads to fibrosis in the larynx have been investigated in human and rodent larynges in vivo, as well as a fibroblast culture model in vitro . Histologic changes in laryngeal muscle after irradiation have also been investigated, and reduction of muscle fibers in irradiated VFs has been shown to be involved in decreased vocal functions after radiotherapy …”
Section: Introductionmentioning
confidence: 99%
“…Further studies have shown significant decreases in the frequency of functional swallows (i.e., no aspiration and minimal residue) and in the portion of patients tolerating normal diets, at 3-and 12-months post-radiotherapy (Logemann et al, 2008). Histological studies of intrinsic laryngeal muscles have shown significant changes in fibril organization and reductions in the average area occupied by muscle fibers 7 to 15 months postradiotherapy (Tedla et al, 2012). These late effects appear to coincide with the disruptions in swallow and breathing described previously (Brodsky et al, 2010).…”
Section: Radiation Injury and Its Late Effectsmentioning
confidence: 99%